Per un’etnografia sperimentale. Riflessioni a partire dall’esperienza di un’antropologa nell’accoglienza - Cammelli, Maddalena Gretel (Antropologia Pubblica, 2017)
This paper seeks to give ethnographic evidence of the role played by anthropological knowledge when involved with asylum seekers reception centres. Moving from an engaged, action-oriented anthropology, with the purpose of working “with” the community where the anthropologist is living, in the following pages I illustrate some situations I lived while working in the emergency program of Italian asylum seekers reception centres. Knowledge, power, community and networks are some of the tools used to illustrate how an anthropologist working in this context can promote processes of concrete experimentation of the anthropological critique in the daily life of working places.